Compound Effects of Flood Drivers and Wetland Elevation Correction on Coastal Flood Hazard Assessment. Issue 7 (4th July 2020) - Muñoz, D. F.; Moftakhari, H.; Moradkhani, H.
Abstract: Compound flooding frequently threatens life and assets of people who live in low‐lying coastal regions. Co‐occurrence or sequence of extremes (e.g., high river discharge and extreme coastal water level) is of paramount importance as it may result in flood hazards with potential impacts larger than each extreme in isolation. Here, we use a coupled approach, that is, bivariate statistical analysis linked to hydrodynamic modeling, to quantify compounding effects of flood drivers and generate flood hazard maps near Savannah, Georgia. Also, we integrate wetland elevation correction in digital elevation models to improve hydrodynamic simulations of compound events and hence the accuracy of flood hazard (inundation and velocity) maps. Using statistical measures, we analyze compounding effects of terrestrial/coastal flood drivers and wetland elevation correction on maximum floodwater height (MFH) and velocity (MFV) for 50‐year return period scenarios. In addition, we compare our results to MFH and MFV patterns of Hurricane Matthew that hit the West Atlantic Coasts on October 2016. The statistical measures indicate significant differences among the scenarios, partly explained by wetland elevation correction. Inundation and velocity maps suggest that a proposed composite, that is, synthesis of marginal Q, marginal H, and "AND" scenarios, can lead to the lowest average underestimation of MFH (−0.35 m) and overestimation of MFV (0.20 m/s) within wetland areas. We conclude that a thorough compound flooding assessment should leverage statistical analysis and hydrodynamic modeling of extremes including corrections of coastal digital elevation models. Key Points: Compound flooding assessment can benefit from statistical methods and physically based modeling including correction of elevation data Coincidence likelihood of hazard drivers and elevation error may dominate the overall uncertainty of maximum floodwater height and velocity Wetland elevation correction in digital elevation models can help improve the overall accuracy of coastal flood hazard maps